2009
DOI: 10.1016/j.biopsych.2009.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Amygdala-Prefrontal Effective Connectivity to Happy Faces Differentiates Bipolar from Major Depression

Abstract: Background-Bipolar disorder is frequently misdiagnosed as major depressive disorder delaying appropriate treatment and worsening outcome for many bipolar individuals. Emotion dysregulation is a core feature of bipolar disorder. Measures of dysfunction in neural systems supporting emotion regulation may therefore help discriminate bipolar from major depressive disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
232
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(252 citation statements)
references
References 52 publications
16
232
3
1
Order By: Relevance
“…An alternative interpretation of these results could be greater abnormal regulation processes in BD. Different studies reported changes in prefrontal regulation in affective disorders that differentiates UD and BD, particular connectivity patterns between the orbital frontal cortex and the amygdala (Almeida et al, 2009;Robinson et al, 2008). Similar processes could be in play in the context of reward processing, meaning that the reported result of a most blunted NAcc activity is not necessarily related to reward outcome, but with regulation abnormalities that take part before the outcome processing.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 98%
“…An alternative interpretation of these results could be greater abnormal regulation processes in BD. Different studies reported changes in prefrontal regulation in affective disorders that differentiates UD and BD, particular connectivity patterns between the orbital frontal cortex and the amygdala (Almeida et al, 2009;Robinson et al, 2008). Similar processes could be in play in the context of reward processing, meaning that the reported result of a most blunted NAcc activity is not necessarily related to reward outcome, but with regulation abnormalities that take part before the outcome processing.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 98%
“…For example, studies have shown decreased connectivity between the anterior cingulate cortex (ACC) and amygdala in response to negative stimuli in unmedicated individuals with MDD. 13,14 Almeida and colleagues 15 reported reduced amygdala-left orbitomedial prefrontal functional connectivity during processing of happy and sad faces in medi cated patients with MDD. However, increased connectivity between frontal cortices, including the medial PFC and rostral ACC, and the amygdala when processing negative words has also been reported in depressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorder patients exhibited elevated functional connectivity between MPFC and amygdala while viewing sad stimuli compared with healthy controls (Versace et al, 2010). Effective connectivity between MPFC and amygdala has been shown to differentiate bipolar disorder from major depression patients (Almeida et al, 2009). These results suggest that MPFClimbic connectivity may underlie the affective disturbance in bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%